OPTIMALISASI PEMBERIAN EDUKASI SENAM IBU HAMIL TERHADAP PENGETAHUAN KEJADIAN RUPTURE PERINEUM DI SITUASI KRISIS KESEHATAN DI PUSKESMAS ANTANG PERUMNAS TAHUN 2024 - Nanda, Kiki Riskianti; Salim, Agus; Yahya, Fajar Dhini; Suriyani, Suriyani (JURNAL KESEHATAN DELIMA PELAMONIA, 2025)
Background: Childbirth often causes perineal tears (perineal rupture) which can cause bleeding, where perineal tears are caused by rupture of the tissue of the birth canal. One way to prevent perineal rupture is to strengthen and maintain the elasticity of the perineum through pregnancy exercises. Objective: This study aims to determine the optimization of providing exercise education for pregnant women regarding knowledge of perineal rupture incidents in health crisis situations at the Antang Perumnas Community Health Center. Research design: used in this research is observational analytics using quantitative data using a cross sectional approach which aims to determine the effect of providing pregnancy exercise education on knowledge of perineal rupture incidents at the Antang Perumnas Community Health Center. Research results: This shows that the p-value of the influence of pregnancy exercise education on the level of knowledge of perineal rupture in crisis situations is 0.000. Because p<0.05, Ha is accepted. H0 is rejected. So it can be concluded that there is an influence of pregnancy exercise education on the level of knowledge of perineal rupture in health crisis situations at the Antang Perumnas Health Center in 2024.